Gambaran Tingkat Kepadatan Jentik Nyamuk Aedes Aegypti Di Wilayah Kerja Unit Pelaksana Teknis Kesmas Sukawati I Tahun 2019 - I Gede Octa Putra Pratama; Gusti Ayu Aryasih (Poltekkes Kemenkes Denpasar, 2019)
Abstract. Dengue Fever is serious public health problem the world, especially Indonesia, which located equator with tropical climate. Flick density checks by calculating House Index (HI), Container Index (CI), Breteu Index (BI), Density Figure (DF), Flicking Free Numbers (ABJ). The level larvae density of Aedes aegypti mosquitoes the working area Public Health Unit Sukawati 1 in 2019 was obtained, namely from measurement results House Index, which were 9 houses (9%) which were positive larvae the results of Container Index measurement were 271 containers 100 families and received percentage of 3% . Bruteu Index measurement results get percentage of 9%. For larva free numbers the results obtained much as 91% of these results have not been able to provide that area has not been free from larva free numbers because has not reached required standard must exceed 95%. And for Density Figure inspection, the results of 5.66 combined results from the House Index, Container Index, Bruteu Index from the results interpretation Batuan Village get results exceeding 5 where said that red area disease transmission larvae high, need immediate control. Doing ways such draining the bathtub, always keeping environment clean, always paying attention jars, cleaning flower pots that are inundated sprinkling abate powder